2021
DOI: 10.1007/s10198-021-01282-4
|View full text |Cite
|
Sign up to set email alerts
|

A cost-effectiveness analysis of pembrolizumab with or without chemotherapy for the treatment of patients with metastatic, non-squamous non-small cell lung cancer and high PD-L1 expression in Switzerland

Abstract: Introduction Pembrolizumab monotherapy or in combination with chemotherapy are two new treatment options for patients with metastatic non-squamous non-small cell lung cancer (NSCLC) and high (≥ 50%) programmed death ligand 1 (PD-L1) expression. We conducted a cost-effectiveness analysis for Switzerland comparing these two options but also pembrolizumab to chemotherapy. Methods We constructed a 3-state Markov model with a time horizon of 10 years. Parametri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…The results of the cost-effectiveness analysis suggested that pembrolizumab monotherapy was more likely to be cost-effective in Switzerland, the United States, France, and Hong Kong, whereas the studies conducted in the background of the United Kingdom, mainland China, and Singapore indicated the contrary. Among these, two studies ( 23 , 24 ) from the perspective of Swiss payers reached ICERs of CHF 68,580 (USD 73,813)/QALY and CHF 57,402 (USD 61,782)/QALY respectively, both below the same WTP. The UK perspective of the study by Georgieva et al.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the cost-effectiveness analysis suggested that pembrolizumab monotherapy was more likely to be cost-effective in Switzerland, the United States, France, and Hong Kong, whereas the studies conducted in the background of the United Kingdom, mainland China, and Singapore indicated the contrary. Among these, two studies ( 23 , 24 ) from the perspective of Swiss payers reached ICERs of CHF 68,580 (USD 73,813)/QALY and CHF 57,402 (USD 61,782)/QALY respectively, both below the same WTP. The UK perspective of the study by Georgieva et al.…”
Section: Resultsmentioning
confidence: 99%
“…Immunotherapy is an expensive treatment, and its economic impacts need to be considered. In the USA, both monotherapy and combination therapy were suggested to be more cost-effective than chemotherapy [ 18 , 19 ]; however, Barbier et al suggested that the cost-effectiveness of combination therapy is marginal compared to monotherapy in Switzerland [ 20 ]. Moreover, combination therapy is more toxic than monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…outlined in Glick et al [ 26 ]}. The resulting ICERs were compared with a willingness-to-pay (WTP) threshold of Swiss Francs (CHF) 100,000/QALY, which is sometimes tentatively considered in analyses for Switzerland [ 27 29 ]. In an additional analysis, we defined an “average comparator” as a weighted average of the mean costs and QALYs of all six comparators considered in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…outlined in Glick et al [26]}. The resulting ICERs were compared with a willingness-to-pay (WTP) threshold of Swiss Francs (CHF) 100,000/QALY, which is sometimes tentatively considered in analyses for Switzerland [27][28][29].…”
Section: Main Outcomesmentioning
confidence: 99%